Study on Small and Medium-Sized Boats with Ecological Propulsion Systems in Danube Delta Area : Array - Moroșanu, Georgiana-Alexandra; Baroiu, Nicușor (Journal of Danubian Studies and Research, 2021)
The small and medium-sized boats manufacturing industry is developing, being an area in which the finished product results after a lot of work and involvement. The production capacity varies depending on the type, destination and size of the ship and the number of units sold varies from one year to another, identifying an increase in demand in the last 2 years. From a geographical point of view, it can be said that the Danube Delta area is practically a concentrated node of development of this industry. The paper presents some aspects of developing a business in the field of production and services for small and medium-sized boats with ecological propulsion systems.